Melanoma Current Clinical Management and Future Therapeutics - Murph, Mandi (IntechOpen, 2015)
Melanoma - Current Clinical Management and Future Therapeutics serves as an advanced course in melanoma or an addendum to further polish expertise. Sections of the book include a thorough introduction on epidemiology and disease, the current surgical management of melanoma and lymph node dissection, immunotherapy along with drug toxicities and emerging research topics, like RAGE and autotaxin, that have potential therapeutic applications. The chapters in this book explore the most common subtype of melanoma, cutaneous disease, as well as a rare form, acral lentiginous melanoma and even canine tumors. Experts from around the globe contributed chapters, most of which have visual illustrations to depict aspects of disease management and therapy, allowing readers to grasp the advanced concepts presented.